A Critical Discourse Analysis Stereotype and Discrimination in "Green Book" Movie Script by Peter Farelly - Meli Samelia; Ansor Putra (ELITE: Journal of English Language and Literature, 2020)
This study aims to analyze the stereotypes and discrimination that occur in the Green Book movie script. The researcher found many utterances as well as actions that refer to stereotypes and discriminatory behavior committed by white people against black people in America. This study used the qualitative method because qualitative is a procedure that produces descriptive data including written and oral words. The results of this study showed that the Green Book movie script contains three types of discrimination and stereotypes. First, Individual Discrimination is presented in unfair treatment by whites against the main black character, Don Shirley. Second, Institutional Discrimination happened in the police institution where the police imprison Don Shirley who did not commit a crime at all, but only because he was black. Third, Structural Discrimination occurred in the form of policies carried out by majority races which have a negative impact on minority races. In the green Book movie script, structural discrimination is presented in a safe travel guide for black people in southern America, the book also contains such as restaurants, hotels, beauty salons, and then medical stores that are safe for black people to visit. This book was published from 1936 to 1976 during the era of segregation in the United States. As the final result of this research, the researcher found the dominant type of discrimination in the Green Book movie script is Individual Discrimination.